MINDS. JWST-MIRI Observations of a Spatially Resolved Atomic Jet and Polychromatic Molecular Wind toward SY Cha - Kamber R. Schwarz; Matthias Samland; Göran Olofsson; Thomas Henning; Andrew Sellek; Manuel Güdel; Benoît Tabone; Inga Kamp; Pierre-Olivier Lagage; Ewine F. van Dishoeck; Alessio Caratti o Garatti; Adrian M. Glauser; et al. (The Astrophysical Journal)
The removal of angular momentum from protostellar systems drives accretion onto the central star and may drive the dispersal of the protoplanetary disk. Winds and jets can contribute to removing angular momentum from the disk, though the dominant process remains unclear. To date, observational studies of resolved disk winds have mostly targeted highly inclined disks. We report the detection of extended H _2 and [Ne ii ] emission toward the young stellar object SY Cha with the JWST Mid-InfraRed Instrument Medium-Resolution Spectrometer (MIRI-MRS). This is one of the first polychromatic detections of extended H _2 toward a moderately inclined, i  = 51 $\mathop{.}\limits^{\unicode{x000B0}}$ 1, Class II source. We measure the semiopening angle of the H _2 emission and build a rotation diagram to determine the H _2 excitation temperature and abundance. We find a wide semiopening angle, high temperature, and low column density for the H _2 emission, all of which are characteristic of a disk wind. We derive a molecular wind mass loss rate of 3 ± 2 × 10 ^−9 M _⊙ yr ^−1 , which is high compared to the previously derived stellar accretion rate of 6.6 × 10 ^−10 M _⊙ yr ^−1 . This suggests either that the stellar accretion and the disk wind are driven by different mechanisms or that accretion onto the star is highly variable. These observations demonstrate MIRI-MRS's utility in expanding studies of resolved disk winds beyond edge-on sources.